Quantitative phosphoproteomics reveals GSK3A substrate network is involved in the cryodamage of sperm motility. Issue 10 (29th October 2021) - Wang, Jing; Wang, Jing; Wang, Min; Hong, Renyun; Tang, Shanshan; Xu, Yuanhua; Zhao, Xia; Zhou, Tao; Wang, Zibin; Huang, Shaoping
Abstract: During sperm cryopreservation, the most significant phenotype of cryodamage is the decrease in sperm motility. Several proteomics studies have already been performed to search for key regulators at the protein level. However, sperm functions are known to be highly regulated by phosphorylation signaling. Here, we constructed a quantitative phosphoproteome to investigate the expression change of phosphorylated sites during sperm cryopreservation. A total of 3107 phosphorylated sites are identified and 848 of them are found to be significantly differentially expressed (DE). Bioinformatics analysis showed that the corresponding genes of these regulated sites are highly associated with sperm motility, providing a connection between the molecular basis and the phenotype of cryodamage. We then performed kinase enrichment analysis and successfully identified glycogen synthase kinase-3α (GSK3A) as the key kinase that may play an important role in the regulation of sperm motility. We further constructed a GSK3A centric network that could help us better understand the molecular mechanism of cryodamage in sperm motility. Finally, we also verified that GSK3A was abnormally activated during this process. The presented phosphoproteome and functional associations provide abundant research resources for us to learn the regulation of sperm functions, as well as to optimize the cryoprotectant for sperm cryopreservation.